A Critical Analysis of Rejection in Vascularized Composite Allotransplantation: Clinical, Cellular and Molecular Aspects, Current Challenges, and Novel Concepts - Sarhane, Karim A.; Tuffaha, Sami H.; Broyles, Justin M.; Ibrahim, Amir E.; Khalifian, Saami; Baltodano, Pablo; Santiago, Gabriel F.; Alrakan, Mohammad; Ibrahim, Zuhaib (Frontiers in Immunology, 2013)
Advances in microsurgical techniques and immunomodulatory protocols have contributed to the expansion of Vascularized Composite Allotransplantation (VCA) with very encouraging immunological, functional, and cosmetic results. Rejection remains however a major hurdle that portends serious threats to recipients. Rejection features in VCA have been described in a number of studies, and an international consensus on the classification of rejection was established. Unfortunately, current available diagnostic methods carry many shortcomings that, in certain cases, pose a great diagnostic challenge to physicians especially in borderline rejection cases. In this review, we revisit the features of acute skin rejection in hand and face transplantation at the clinical, cellular and molecular levels. The multiple challenges in diagnosing rejection and in defining chronic and antibody-mediated rejection in VCA are then presented, and we finish by analyzing current research directions and novel concepts aiming at improving available diagnostic measures.